IMF Staff Papers : Volume 10, No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1963)
This paper discusses effects of inflation on economic development. A mild inflation may well encourage little, or no, evasion of the 'inflation tax.' On the other hand, a strong inflation, and frequently a mild one also, will lead to community reactions which have effects like those of widespread tax evasion. A development policy may have wider aims than the encouragement of a high level of investment. Inflation has two effects on the desire for liquidity, which are related to the two basic reasons why individuals and businesses wish to hold liquid assets-the speculative and precautionary motives. Inflation increases the value of effective liquidity, thereby raising the community's desire for it, but it makes the most generally accepted store of liquidity unacceptable sources of protection. The control of inflation is only one of the problems facing a government wishing to encourage rapid economic development. The fight against illiteracy, the reform of bureaucratic practices, the building of basic sanitary facilities for the eradication of endemic diseases, the substitution of competitive for monopolistic trade practices, the encouragement of a widespread spirit of entrepreneurship, and the creation of an adequate amount of social capital, may be important prerequisites for rapid growth.